PELATIHAN UU ITE (Informasi dan Transaksi Elektronik) - Rina Isti; Suci Amalia Rizki; Isnaini Aniswati (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2020)
Indonesia as a civilized country has the aspects of life that are protected by the constitution, one of which is the honor and good name. Not only the honor and good name of someone who is still alive, but also people who have died. Along with advances in technology and the development of democracy in Indonesia, many crimes against the honor and good name in the form of insult and defamation, especially those conducted through social media. Currently the law governing defamation is still limited, the Criminal Code is limited to the medium used, while the Act ITE only regulate general insult, so there is no law that specifically regulates insult to people who have died through social media. This paper outlines that an insult to people who have died through social media can be punished by using the rules in the Criminal Code and the ActITE